Liberty intact : human rights in English law - Tugendhat, Michael (Oxford : Oxford University Press, 2017)
Providing a short history of human rights from the eighteenth century to present day, this book traces English Common Law through the French and American declarations of rights, identifying rights which evolved from the English law and politics of the fifteenth century, and which are recognised in the human rights law we see today.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 5, 2017).
Keywords: Human rights -- England; Human rights -- Wales; Law